Hubungan Aktifitas Fisik Ibu Hamil Dengan Konstipasi Masa Kehamilan - Siti Mudlikah; Erda Restiya Agustin; Ida Susila (IJMT : Indonesian Journal of Midwifery Today, 2021)
Constipation occurs in about 11-13% of pregnancies by symptoms of difficulty on defecating, lower abdominal pain and frequency of passing stools of 3 times a week, causing discomfort and anxiety for pregnant women. The study was to determine the relationship between physical activity and constipation.The research method is correlation analytic cross sectional approach. Data retrieval is from June to December 2020 at Praktik Mandiri (midwifery services) at Jatikalang Kec. Prambon, Sidoarjo. Population: All 3rd trimester pregnant women totaled 37 people in 2020, or it is called total population sample. Collecting data is by direct questionnaire on statements of light physical activity, moderate physical activity and heavy physical activity. Data analysis uses simple correlation test statistics.Research results indicate that pregnant women who experience constipation do more light activities are 13 people (100%, moderate physical activity are of 13 people (92.9%) than those who are not constipated on heavy physical activity as many as 10 people (100%), moderate physical activity being 1 person (7.1%).The results of the statistical test of the correlation between physical activity and constipation in pregnant women have positive value of 0.821, indicating very strong correlation between physical activity and constipation, significant (2-tailed) 0.00 < 0.01, the higher the physical activity of pregnant women, the higher the occurrence of constipation.Conclusions from this study; There is a strong relationship between physical activity and constipation in pregnant women, namely light physical activity and moderate physical activity less than 30 minutes at risk of constipation. Suggestions for preventing constipation can be done by doing physical activity more than 30 minutes a day, consuming high-fiber nutritional diet and drinking enough mineral water to prevent constipation in pregnancy.